Factors Influencing Students’ Academic Success in Introductory Chemistry: A Systematic Literature Review - Jessica Chestnut; Carla C. Johnson (Education Sciences)
Undergraduate introductory chemistry is a gatekeeping course preventing students from persisting in STEM degree programs. It is important to understand students’ experiences of introductory chemistry and better support students as this course traditionally has high attrition and failure rates. This systematic literature review examines the factors of academic success for undergraduates in introductory chemistry courses and aims to understand how these factors differ for varying student groups. A meta-analysis of 35 articles uncovered three emergent themes for promoting students’ academic success: course design, instructional tools and resources, and student learning and characteristics. Most notably, active learning environments, metacognitive assessments, and student affective variables such as identity and motivation emerged as significant predictors of students’ academic success. Additionally, this review demonstrates how differences in student demographics, achievement levels, affective variables, and participation in chemistry affect the extent to which students succeed in this course. Student demographics were most frequently reported to cause disparities in course performance, with students from historically underrepresented populations exhibiting the most disadvantages in overall course performance. These findings signify the importance of creating effective learning environments in introductory chemistry for students from diverse backgrounds to achieve equitable outcomes and sustain STEM interest.